Monitoring, Evaluation and Learning in NGO Advocacy - Findings from Comparative Policy Advocacy MEL Review Project - and Coe, Jim; Majot, Juliette (ODI and Oxfam, 2013)
For organizations committed to social change, advocacy often figures as a crucial strategic element. How to assess effectiveness in advocacy is, therefore, important. The usefulness of Monitoring, Evaluation and Learning (MEL) in advocacy are subject to much current debate. Advocacy staff, MEL professionals, senior managers, the funding community, and stakeholders of all kinds are searching for ways to improve practices – and thus their odds of success – in complex and contested advocacy environments. This study considers what a selection of leading advocacy organizations are doing in practice. We set out to identify existing practice and emergent trends in advocacy-related MEL practice, to explore current challenges and innovations. The study presents perceptions of how MEL contributes to advocacy effectiveness, and reviews the resources and structures dedicated to MEL.